2007
DOI: 10.4028/www.scientific.net/kem.353-358.848
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Wear Behavior of Thermally Sprayed Fe-Based Amorphous Coating

Abstract: In this study, microstructure and wear behavior of thermally sprayed Fe-based alloy coatings were investigated. Fe-based alloy coatings were formed on a carbon steel substrate and then heat-treated at temperature of 700 oC for 20 minutes. Dry sliding wear tests were performed using the sliding speeds of 0.4 and 0.8 m/s, the applied loads of 3 and 6 N. Microstructure and wear behavior of as-sprayed and heat-treated Fe-based amorphous coatings were studied using a scanning electron microscope(SEM), transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Synthesizing amorphous and/or nanocrystalline layers on metal substrates can be utilized to improve surface performance such as wear and corrosion resistance (Kim et al;2007). Greer et al reported that amorphous alloys can have very good resistance to sliding and abrasive wear and the coatings can have low friction coefficient (Greer et al;.…”
Section: Amorphous-nanocrystalline Materialsmentioning
confidence: 99%
“…Synthesizing amorphous and/or nanocrystalline layers on metal substrates can be utilized to improve surface performance such as wear and corrosion resistance (Kim et al;2007). Greer et al reported that amorphous alloys can have very good resistance to sliding and abrasive wear and the coatings can have low friction coefficient (Greer et al;.…”
Section: Amorphous-nanocrystalline Materialsmentioning
confidence: 99%
“…It is assumed that the kinetic energy of the particles with high contact pressure promotes bonding with the substrate surface and develops the coating formation [12]. It is assumed that the kinetic energy of the particles with high contact pressure promotes bonding with the substrate surface and develops the coating formation [12].…”
mentioning
confidence: 99%